La expresión plástica y su incidencia en el desarrollo motriz de los niños y niñas de primer año de educación general básica de la escuela “Gabriela Mistral n° 1” del cantón Catamayo, provincia de Loja, periodo lectivo 2012-2013 - Martínez Carrión, Zoila Editha (2013)
The present denominated thesis "THE PLASTIC EXPRESSION AND THEIR INCIDENCE IN THE MOTIVE DEVELOPMENT OF THE CHILDREN AND GIRLS OF FIRST YEAR OF BASIC GENERAL EDUCATION OF THE SCHOOL "GABRIELA MISTRAL N° 1" OF THE CANTON CATAMAYO, COUNTY DE LOJA, PERIOD LECTIVO 2012-2013" it has been structured and developed according to the regulations of graduation of the National University of Loja. The general objective that guided the investigation was: To investigate the incidence of the Plastic Expression in the Motive Development of the children and First year-old girls. The methods used for the elaboration of the present investigative work were: Scientific, Inductive, Deductive and the Statistical Pattern; the used techniques were: a Survey directed to the Teachers First years old the types of Plastic Expression that use in the daily day of work those with the children and girls and the Test of Motive Ability of Oseretzky applied the children and girls to determine the Motive Development to settle down. In the implementation of the survey to teachers concluded that: 100% of teachers use in their daily work drawing and painting and 50% use the sculpture, photography and ceramics. Since these types of Plastic Expression Motor stimulate growth as the basis for the feelings, perceptions, and thoughts, and in this way create and express what they feel and achieve autonomy while others relate to. According to the results of the Motive Test of Ozeretzki you reaches the conclusion that: 59% of children and investigated girls carried out the six tests proposals correctly for what their Motive Development is appreciated as Satisfactory; and, 41% of children and girls could not carry out the six tests correctly for what their Motive Development is appreciated how Not Satisfactory. Through the Motive Development the children and girls experience the world that surrounds them and they know this way the limits of their body and their capacities; this knowledge provides them autonomy and therefore security and self-esteem.